Harmonic analysis in phase space - Folland Gerald B (Princeton Princeton Univ Press, 1989)
This book provides the first coherent account of the area of analysis that involves the Heisenberg group, quantization, the Weyl calculus, the metaplectic representation, wave packets, and related concepts. This circle of ideas comes principally from mat
Keywords: Harmonic analysis; Phase space(Statistical physics)